2008
DOI: 10.1128/aem.01709-07
|View full text |Cite
|
Sign up to set email alerts
|

Intact Membrane Lipids of “ Candidatus Nitrosopumilus maritimus,” a Cultivated Representative of the Cosmopolitan Mesophilic Group I Crenarchaeota

Abstract: In this study we analyzed the membrane lipid composition of "Candidatus Nitrosopumilus maritimus," the only cultivated representative of the cosmopolitan group I crenarchaeota and the only mesophilic isolate of the phylum Crenarchaeota. The core lipids of "Ca. Nitrosopumilus maritimus" consisted of glycerol dialkyl glycerol tetraethers (GDGTs) with zero to four cyclopentyl moieties. Crenarchaeol, a unique GDGT containing a cyclohexyl moiety in addition to four cyclopentyl moieties, was the most abundant GDGT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 184 publications
(196 citation statements)
references
References 35 publications
8
183
0
Order By: Relevance
“…5). Nevertheless, the TEX 86 of IPL-derived GDGTs was consistently higher than that of the CL-GDGTs, which has been observed previously in other settings (Schubotz et al, 2009;Lipp and Hinrichs, 2009 Schouten et al (2008) and reported that GDGT-1 is mainly associated with the HPHIPLs while GDGT-2, -3 and -4 are mainly associated with the DH-headgroup in (enrichment) cultures of Thaumarchaeota. A more rapid lysis of the HPH-GDGTs, as observed in this study and that of Schouten et al (2012), will preferentially remove GDGT-1 from the pool of IPLGDGTs and bring it into the pool of CL-GDGTs.…”
Section: Implications For the Tex 86 Paleothermometermentioning
confidence: 51%
See 3 more Smart Citations
“…5). Nevertheless, the TEX 86 of IPL-derived GDGTs was consistently higher than that of the CL-GDGTs, which has been observed previously in other settings (Schubotz et al, 2009;Lipp and Hinrichs, 2009 Schouten et al (2008) and reported that GDGT-1 is mainly associated with the HPHIPLs while GDGT-2, -3 and -4 are mainly associated with the DH-headgroup in (enrichment) cultures of Thaumarchaeota. A more rapid lysis of the HPH-GDGTs, as observed in this study and that of Schouten et al (2012), will preferentially remove GDGT-1 from the pool of IPLGDGTs and bring it into the pool of CL-GDGTs.…”
Section: Implications For the Tex 86 Paleothermometermentioning
confidence: 51%
“…Lipp and Hinrichs, 2009;Liu et al, 2011). Ammonia-oxidizing Archaea, whose IPLs consist mainly of GDGTs with MH-, DH-and HPH-as well as an unknown headgroup (Sinninghe Damsté et al, 2002b;Schouten et al, 2008;Pitcher et al, 2010, are ubiquitous and active in marine surface sediments (Francis et al, 2005;Caffrey et al, 2007;Park et al, 2008Park et al, , 2010. Since archaeal ammonia-oxidation proceeds aerobically (Kö nneke et al, 2005;Hatzenpichler et al, 2008;Erguder et al, 2009;Park et al, 2010) and also in environments with low oxygen concentrations ranging from <3 lM to 0.2 mM, we expected in situ production of crenarchaeol-IPLs in (sub-) surface layers where low amounts of oxygen were still present, i.e.…”
Section: Sedimentary Production and Preservation Of Gdgtsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPLs were extracted from freeze-dried filters using a modified Bligh and Dyer technique (Bligh and Dyer, 1959) as described by Schouten et al (2008). Analysis of crenarchaeol-based IPLs (crenarchaeol-hexose, crenarchaeol-dihexose, crenarchaeol-hexose-phosphohexose, crenarchaeol-hexose-'176', crenarchaeol-dihexose-'176'; '176' represents an unknown headgroup with a mass of 176 Da) and crenarchaeol-hexose-'180' (representing a major IPL in Nitrosopumilus maritimus SCM1; Prosser and Nicol, 2008) was achieved by HPLC/electrospray ionization/MS/MS in selected reaction monitoring (SRM) mode using chromatographic conditions and source settings as described by Schouten et al (2008).…”
Section: Extraction and Analysis Of Iplsmentioning
confidence: 99%